Popliteal Artery Diameter: A Cadaveric Study - Ujwal Gajbe1, Brijraj Singh2 , Nandkishor Bankar3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Femoral artery proceeds as a popliteal artery from the osseo-aponeurotic opening of theadductor magnus to the caudal margin of the popliteal muscle. It passes through the adductor canal, theadductor hiatus then through the popliteal fossa ends at the lower margin of the popliteal muscle, in furthercourse it divided into the anterior and posterior tibial arteries. Popliteal aneurysm i.e. abnormal dilation ofthe whole or part of the popliteal artery causes edema and pain in the popliteal fossa. The popliteal arteryserves as bypass grafts in specific location i.e. above or below-knee. It is also often affected by penetratingand blunt trauma of the lower limb. As a consequence, the exposure of this artery is frequently and neededexploration of either in emergency or in elective vascular procedures.Material and Method: The present Study was carried out in the department of anatomy at Jawaharlal NehruMedical College in Collaboration with department of anatomy and Datta Meghe Medical College, NagpurMaharashtra. Total 102 lower limbs of 51 cadavers were included in the study.Observation and Results: In males the mean diameter of popliteal artery at it origin is 6.7 ± 0.7mm onright and 6.6 ± 0.6 mm on left respectively, whereas in females the mean diameter on right is noted as 6.4± 0.5 mm and on left it is 6.2 ± 0.3mm. At proximal to termination the mean diameter of popliteal artery inmales is observed to be 6.9 ± 0.7mm on right and 6.8 ± 0.7mm on left, while in females it is noted to be 6.6± 0.5mm on right and 6.4 ± 0.4mm on left respectively.Conclusion: To conclude the data from the present study is useful for the vascular surgeons, radiologists.